Barakayeva HOW TO MOTIVATE STUDENTS TO LEARN ENGLISH? HOW TO MOTIVATE STUDENTS TO LEARN ENGLISH? - Barakaeva D, DBarakaeva (Журнал иностранных языков и лингвистики, 2022)
Motivation can be seen as a force that moves a person to initiate an action and to keep on until the goals are achieved.